Entre la autoficción y la teoría expresiva del arte: "Efectos del amor propio" de Miguel Álvarez de Sotomayor (c. 1810) - Muñoz de Morales Galiana, Javier (2022)
This paper aims to carry out an analysis of the novel Efectos del amor propio (c. 1810) using a broader theoretical framework than the one that has been used so far to study it. Thus, we consider that it can be typified as “autofiction”, a type of novel in which the identity of the main character and that of the author are mixed up, and which is conditioned by a new way of understanding artistic creation that emerged in the early nineteenth century: the “expressive theory of art”, applicable to works whose main purpose was the intimate venting of the author.